Decamethoxin and chlorhexidine bigluconate effect on the adhesive and biofilm-forming properties of Streptococcus mitis - Faustova, Mariia O.; Chumak, Yuliia V.; Loban’, Galina A.; Ananieva, Maiia M.; Havryliev, Viktor M. (Frontiers in Oral Health, 2023)
The aim of the study was to investigate the effect of antiseptics on the adhesive and biofilmforming properties of clinical S.mitis isolates isolated from the oral cavity of patients with an infectious and inflammatory post-extraction complication.Materials and methods. Twenty four clinical isolates of S.mitis isolated from patients were studied. The studied antiseptics included 0.02% aqueous solution of decamethoxin and 0.05% solution of chlorhexidine bigluconate. Adhesion of clinical isolates under the action of decamethoxin and chlorhexidine bigluconate was determined by the method of V.I. Brillis. The biofilm-forming properties of clinical isolates were studied using the "microtiter plate test" according to G.D. Christensen.Results. The studied clinical isolates of S.mitis are classified as highly adherent microorganisms. Action of decamethoxin on clinical isolates decreases the adhesion index of the studied isolates in comparison with the adhesion index of the control culture. Action of chlorhexidine bigluconate on S.mitis isolates increases of adhession of the studied clinical isolates in comparison with the control. After the effect of decamethoxin, the optical density of clinical isolates decreased considering the optical density results of the control. The clinical isolates left an average film-forming capacity even after chlorhexidine bigluconate action.Conclusions. Clinical isolates of S.mitis are highly adherent microorganisms. The antiseptic decamethoxin decreases the adhesion index of these bacteria, while chlorhexidine bigluconate increases the adhesion index of clinical S.mitis isolates. Clinical S. mitis isolates have an average biofilm formation capacity index. The antiseptic decamethoxin inhibits the biofilm formation capacity of S.mitis from medium to low.